Parapharyngeal Tumour A Study of 30 Cases - Bhowmik, Bithi; Ahmed, Miraj; Talukder, Debesh Chandra; Siddique, Belayet Hossain (Delta Medical College Journal, 2016)
Background: Parapharyngeal tumours are a group of rare neoplasms arising from structures within the parapharyngeal space. The complex anatomical and pathological consideration of this region often present a substantial challenge to the otolaryngologist and head-neck surgeons in the evaluation and management of these lesions. The majority of tumours arising in the parapharyngeal space are benign and surgical resection is the mainstay of treatment Objective: To determine frequency, demography, histological pattern and management of parapharyngeal tumour. Materials and method: A cross sectional study was carried out from January 2007 to December 2007. Total 30 cases were selected from Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, Dhaka Medical College Hospital, Dhaka, Bangladesh and Sir Salimullah Medical College Mitford Hospital, Dhaka, Bangladesh. Results: In this study 37% patients were in the fourth decade. Among the study subjects, 21(70%) were male and 9(30%) were female. Most of the patients presented with neck swelling (66%) followed by oropharyngeal swelling (50%). In this study salivary gland tumours were the highest (47%) in number, neurogenic tumours constituted 40% and chemodectomas were 13%. Histopathologically 80% tumours were benign. Both transparotid and inferior approaches were used for surgical resection in each 40% of cases. Conclusion: Most of the cases were benign and detected around fourth decade of life with male predominance. Surgical resection was the lone treatment for the cases with few post operative complications. Delta Med Col J. Jan 2016 4(1): 18-23